An illustrated guide to cocktails : 50 classic cocktail recipes, tips, and tales - Shtuhl, Orr (Gotham Books, 2013)
"An intoxicating tribute to cocktails, featuring colorful histories, charming illustrations, and delectable recipes Shaken or stirred, on the rocks or straight up, every cocktail has a unique history. Bringing this rich lore to life, An Illustrated Guide to Cocktails showcases the often romantic origin of classic and modern mixed drinks and the fascinating characters who made them famous. From the crooked gangster who inspired the Jack Rose (a drink often served in Manhattan's gilded Astor mansion during the Jazz Age) to the legendary Margarita (associated with the Tijuana dancer now known by her stage name, Rita Hayworth), the spirited blend of alcohol and alchemy is showcased on each beautifully illustrated page. The drink recipes include favorite classics (such as Old Fashion, White Russian, Sidecar) alongside forgotten standards such as the Blood and Sand. With guides to various spirits, suggestions for stocking your home bar, and mixing tips and techniques, An Illustrated Guide to Cocktails brings the marvels of mixology to every home bartender"--